Diagnóstico da sustentabilidade de agroecossistemas: bairros rurais e assentamentos de reforma agrária do município de Araras, SP - Cunha, Cristiano Pereira da (Universidade Federal de São Carlos, 2013)
This work presents the results of the research on agriculture in Araras city, São Paulo, Brazil. It aims to assess evaluation of sustainability of agroecossystems in territories of familiar farmers and to identify their impacts, demands and alternatives to overcome the identified problems. MESMIS methodology and research-action were, simultaneously and complementary, used to investigate them. The first, while consolidated procedure to evaluate agroecossystems sustainability; the second, as farmers and researchers identified problems and implemented actions in order to minimize or overcome them. Longitudinal analysis of agriculture evolution is based on data by Instituto Brasileiro de Geografia e Estatística from 1960 to 2006 and from Censitary Mapping of Agropecuary Productive Areas of São Paulo State 2007/2008. Transversal analysis refer to 81 evaluated agroecossystems in territories of São Bento district and region, Caio Prado district and Araras 2, 3, 4 and 5 rural settlements, evaluated for economic, sociocultural and productive dimensions. The agricultural pattern revealed for districts is predominantly characterized by specialization in permanent monocultures such as avocado and citriculture, intensive use of machinery, basically operated by familiar workforce; and dependent on external inputs. Rural settlements represent return to life in rural environment, strategies used by traditional familiar farmers are different from those of district farmers, with production of subsistence cultures (manioc, corn, bean), horticultural products and animal breeding. For evaluated territories, selfconsumption is prevalent among settled familiar farmers. Direct viii commercialization and difficulty to access machinery and inputs are determinant factors in defining settled familiar farmers as preferred beneficiaries for public policy focusing on agroecology.
Diagnosis of sustainability in agroecosystems: rural districts and agrarian reform rural settlements in Araras city, SP.
Keywords: Agroecologia; Agroecossistemas; Agricultura familiar; Assentamentos rurais; Desenvolvimento territorial; Araras (SP); CIENCIAS AGRARIAS